Militarisering av Åland – möjlighet, eller brott mot internationell rätt? - Taivassalo,Walter Neil Gordon (2025)
The security in Europe has changed dramatically during recent years, with the two most significant changes being Russia’s invasion of Ukraine, and NATO:s expansion with Sweden and Finland as new member states. The increasing militarization in Europe has also brought back an old question into the public debate, namely if the Åland islands should be re-militarized with the purpose of securing the Baltic Sea militarily. The question has been discussed in both Swedish and Finnish media, and in Finland it has also been a part of the political discussion, for example in the most recent presidential election (in 2024). Åland has been demilitarized since the year 1856, but over the years there have been several exceptions from the demilitarization made. Changing circumstances and shifting power-dynamics in the Baltic Sea region has resulted in the question of demilitarization repeatedly resurfacing over the years. The demilitarization of Åland is primarily regulated by old interna-tional agreements, but also by state practice. The purpose of this thesis is to research if it is possible for Finland to in accordance with international law withdraw from the demilitarization and remilitarize Åland. The premise is that the treaties that regulate the demili-tarization are the law in force, but the thesis will examine to which degree these treaties in whole or in part have become obsolete, which obligations arise from state practice according to customary law, and lastly, what op-portunities general treaty law provides for terminating these treaty obliga-tions. The thesis shows that the treaties that regulate Åland’s demilitarization are still to be regarded as valid in accordance with international law. The trea-ties are in certain parts obsolete, but not to such extent that it would result in the termination of the treaties as a whole, since these obsolete parts don’t conflict with the general purpose of preserving the demilitarization and neutralization of Åland. This general purpose has also become a part of the regional customary law through repeated confirmation of the continued validity of the demilitarization. The applicable customary law also means that Finland cannot simply withdraw from the treaties, as they would still be bound to the treaty through international custom according to interna-tional law. The changed circumstances are thus not significant enough to change the legal status of Åland, unless something as unlikely as if all parties to all treaties regulating Åland’s legal status were to enter a new treaty that ter-minates or replaces the old ones, and thus also creating a new customary law. However, this thesis also shows that it is not impossible that changing circumstances in the future may yet come to affect Åland’s legal status. If such circumstances occur it will be up to the lawyers of the future to once again examine this recurring question and come to a new, or the same, conclusion.
Keywords: folkrätt; Åland